2019
DOI: 10.1016/j.cocom.2019.e00383
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of structural and vibrational properties of SrHfO3 compared to SrZrO3

Abstract: a b s t r a c tThe structural and vibrational properties of SrHfO 3 compared to those of the SrZrO 3 were investigated using first-principles calculations. The phonon dispersion curves, reported in the high-symmetry cubic perovskite phase, point out the coexistence of structural antiferrodistortive instabilities at the R and M zone-boundary points and a ferroelectric instability at the zone center. Different possible intermediate phases are characterized by comparing their internal energies, giving the same hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…The tireless efforts of dedicated researchers enable the thorough investigation of these materials in a wide range of applications. Considering that most material properties are determined by their phase stability, it is crucial to thoroughly investigate these phase stabilities before analyzing any other characteristics [7][8][9]. Using e cient and cost-effective software is a wise approach before investing signi cant resources into experimental projects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tireless efforts of dedicated researchers enable the thorough investigation of these materials in a wide range of applications. Considering that most material properties are determined by their phase stability, it is crucial to thoroughly investigate these phase stabilities before analyzing any other characteristics [7][8][9]. Using e cient and cost-effective software is a wise approach before investing signi cant resources into experimental projects.…”
Section: Introductionmentioning
confidence: 99%
“…The perovskite materials have gained considerable recognition due to different technological elds. The formula ABO 3 is commonly employed in the identi cation of oxide-perovskites [10][11][12]. In this context, the symbol A is often used to represent alkaline earth metals, including calcium, magnesium, beryllium, barium, radium, and various others.…”
Section: Introductionmentioning
confidence: 99%
“…SrZrO 3 (SZO) is a perovskite structure compound with a low dielectric constant of 20–50 . Bulk SZO undergoes a series of phase transitions as the temperature decreases, but no ferroelectric phase transition occurs until the temperature drops to 0 K, and the ferroelectric state is completely suppressed due to antiferrodistortive instabilities and/or quantum fluctuations. The orthorhombic space group ( Pbnm ) and a – a – c + tilting pattern (marked by Glazer notation) are shared by bulk SZO and CaTiO 3 . , Experimental research and calculation analysis indicated that epitaxial strain can stabilize the ferroelectric state of CaTiO 3 . , The biaxial tensile strain imposed by the substrate can inhibit the octahedral tilt in the CaTiO 3 , resulting in ferroelectricity with a remanent polarization value of approximately 5 μC/cm 2 (10 K) . The optical second harmonic generation (SHG) measurement shows a tetragonal-like polar behavior in CaTiO 3 films subjected to a compressive strain .…”
Section: Introductionmentioning
confidence: 99%
“…Cubic BaHfO 3 considered as ABO 3 perovskite oxides, where an A atom positioned at (0,0,0) corner of cube , a B atom at body center position(1/2, 1/2, 1/2), and three O atoms at face centered positions(1/2, 1/2, 0) forming a BO 6 regular octahedron [2].…”
Section: Introductionmentioning
confidence: 99%